2014
DOI: 10.1002/app.41027
|View full text |Cite
|
Sign up to set email alerts
|

A method for scale‐up of co‐electrospun nanofibers via flat core‐shell structure spinneret

Abstract: An approach to the scale‐up of co‐electrospinning via a flat core‐shell structure spinneret has been developed in this study. The spinneret with a flat surface involves shell‐holes and core‐needles. Electric field simulation reveals that the flat core‐shell spinneret configuration creates a more uniform electric field gradient. Experimental study shows that in comparison with the conventional needle co‐electrospinning, core‐shell nanofibers produced by this new designed setup are finer and of better morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…We believe that the formation of these coils results from the interface interaction of the TPU phase and the Nomex phase due to their nonuniform shrinking behavior. In our previous study, the jets formed from a coaxial spinneret and a single-needle spinneret of the electrospinning systems have been shown. The deflection of the jet at the beginning stage of the spinning process is not observed in coaxial and single-needle electrospinning.…”
Section: Results and Discussionmentioning
confidence: 98%
“…We believe that the formation of these coils results from the interface interaction of the TPU phase and the Nomex phase due to their nonuniform shrinking behavior. In our previous study, the jets formed from a coaxial spinneret and a single-needle spinneret of the electrospinning systems have been shown. The deflection of the jet at the beginning stage of the spinning process is not observed in coaxial and single-needle electrospinning.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The coaxial spinneret, the key factor in producing core−shell fibers and one of the most important factors influencing the morphology and property of core−shell fiber, has attracted the great interest of researchers. Wu et al developed a flat core− shell structure spinneret with a flat surface, 16 and found that core−shell fibers produced by this spinneret were finer and exhibited better morphology compared with conventional needle coelectrospinning. Rahimi and Mokhtari 17 declared that the inner nozzle lengths of coaxial nozzles had an enormous impact on structured core−shell hexadecane−polyurethane nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [13] designed a new multihole spinneret with equilateral hexagon hole array to meet a highproduction requirement and high quality of nanofibers. Wu et al [14] developed an approach to the scale-up of co-electrospinning via a flat core-shell structure spinneret which has a flat surface involves shell holes and core needles to fabricate composite nanofibers with special morphologies.…”
Section: Introductionmentioning
confidence: 99%